Shopping preferences at Shopee Barokah on products perspective of Islamic economy: the effect of promotion and halal lifestyle Bandar Lampung community / Dwi Kurniasari, Budimansyah and Dimas Pratomo - Kurniasari, Dwi; Budimansyah; Pratomo, Dimas (Universiti Teknologi Mara Selangor, 2023)
Recently, the Halal Lifestyle of the Muslim community has been very careful in doing online shopping, this is because of the promotion and demand for the Islamic market, it turns out that halal products have not yet flooded the ecommerce market in Indonesia, while cases that often occur are falsification of halal certificates, halal sticker logo, even mixing non-halal raw materials with halal raw materials. This study uses a quantitative approach. The population in this study is the Bandar Lampung community. Sampling was carried out using a purposive sampling technique with 400 samples as respondents. The data used in this study were obtained from distributing questionnaires. The results of the data obtained that the promotion variable has a negative and significant effect on shopping preferences. And the halal lifestyle variable has a positive and significant effect on shopping preferences. The results of the product moderation test on the relationship between promotion and halal lifestyle towards shopping preferences produce a significant value, which means that the product strengthens the relationship between promotion and halal lifestyle towards shopping preferences.